2016
DOI: 10.1021/acscatal.6b00271
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Kinetic Resolution of 3-Aryl-4-pentenoic Acids

Abstract: The first example of dynamic kinetic resolution (DKR) of chiral unsaturated carboxylic acids is described. The application of tandem metal–enzyme DKR is a powerful tool for the manufacture of high-value chemical commodities. This new protocol of kinetic resolution based on irreversible enzymatic esterification of 3-aryl-4-pentenoic acids with ortho esters was introduced to obtain optically active unsaturated carboxylic acids. This procedure was combined with metal-catalyzed racemization of the target substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 105 publications
1
8
0
Order By: Relevance
“…In our primary studies, we found that the Novozym 435-catalyzed polycondensation between racemic Asp diesters and achiral diols was not successful, because Novozym 435 showed a high preference for l -Asp diesters and the chain growth reaction was stopped when slow-reacting d -Asp diesters locating at the chain terminal. This problem was similar to that one observed in Novozym 435-catalyzed ROP of 6-MeCL and polycondensation of racemic diols and dicarboxylic acid derivatives. , However, the strategy proposed by Meijer and Heise was not efficient in this case because of the difficult racemization of general racemic acid derivatives without the α-electron-withdrawing group . Herein, this paper reports Novozym 435-catalyzed preparation of various chiral polyesters with high optical purity and high molecular weight starting from diols and l - or d -Asp diesters with different N -substituents.…”
Section: Introductionsupporting
confidence: 57%
“…In our primary studies, we found that the Novozym 435-catalyzed polycondensation between racemic Asp diesters and achiral diols was not successful, because Novozym 435 showed a high preference for l -Asp diesters and the chain growth reaction was stopped when slow-reacting d -Asp diesters locating at the chain terminal. This problem was similar to that one observed in Novozym 435-catalyzed ROP of 6-MeCL and polycondensation of racemic diols and dicarboxylic acid derivatives. , However, the strategy proposed by Meijer and Heise was not efficient in this case because of the difficult racemization of general racemic acid derivatives without the α-electron-withdrawing group . Herein, this paper reports Novozym 435-catalyzed preparation of various chiral polyesters with high optical purity and high molecular weight starting from diols and l - or d -Asp diesters with different N -substituents.…”
Section: Introductionsupporting
confidence: 57%
“…Heteroleptic dirhodium complexes for highly enantioselective processes start to appear [105] . Dirhodium compounds can be used as catalysts for hydrogenation of alkenes [106] (such reactions were proposed to proceed via heterolytic splitting of hydrogen by the dirhodium complex) or can be used as catalysts for transfer hydrogenations [107] , dynamic kinetic resolution of alcohols, DKR of homoallyl‐carboxylic acids [108] or as catalysts in other processes as hydroformylation of alkenes [109,274] or reduction of CO 2 with silanes [110] . Photochemical and thermal evolution of molecular hydrogen from water [111] can be catalyzed with dirhodium paddlewheel complexes with electron withdrawing carboxylate ligands [112] .…”
Section: Applications Of Dirhodium(iiii) Complexesmentioning
confidence: 99%
“…Other metals that have been recently used in chemoenzymatic transformations are Rh, [73] Pt, [74] and Co [75] . However, these reactions were performed in a telescopic or in a non‐stereoselective fashion, out of the scope of this minireview, although it is expected that in the close future examples of asymmetric cascades using these metals will be described [76] …”
Section: Metal‐enzyme Cascade Processesmentioning
confidence: 99%